Mangrove species of Mantehage Island, Bunaken National Park, North Sulawesi, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Djamaluddin R, Djabar B. 2022. Mangrove species of Mantehage Island, Bunaken National Park, North Sulawesi, Indonesia. Biodiversitas 23: 2845-2852. A study on mangrove species in Mantehage Island, Bunaken National Park, North Sulawesi, Indonesia, is important due to the large extent of mangrove forest, geographical position, and geomorphological characteristics of the island. Many mangrove species are expected to occur on this island. This study was conducted to explore the biological diversity of mangrove species and to evaluate the biogeography and conservation status of certain species occurring on this island. Extensive surveys were conducted throughout the island on the areas covered with mangroves, with a total of 58 locations surveyed using spot check and quadrat-transect methods, and species identification was based on morphological characteristics. Results showed that in Mantehage Island there were 20 species of true mangrove belonging to 13 genera and 11 families, including Acanthus ilicifolius L., Acrostichum spesiosum Willd., Aegiceras corniculatum (L.) Blanco, Avicennia marina (Forsk.) Vierh., Bruguiera gymnorrhiza (L.) Lamk., Bruguiera parvilora Weight & Arnold ex Griffith, Ceriops tagal (Perr.) C.B. Rob, Excoecaria agallocha L., Heritiera littoralis Dryand, Nypa fruticans (Thunb.) Wurmb., Rhizophora apiculata Bl., Rhizophora mucronata Lamk., Rhizophora stylosa Griff., Scyphiphora hydrophyllacea Gaertn., Sonneratia alba J. Smith, Sonneratia ovata Blake., Xylocarpus granatum K?enig. Three rare species in the mangrove of Bunaken National Park, Camptostemon philippinense (Vidal) Becc., Bruguiera cylindrica (L.) Bl. and Lumnitzera racemosa Willd. were also recorded. The presence of C. philippinense could explain its distribution limit on the northern coast of North Sulawesi. Indication of putative hybrids in the genera of Rhizophora was found, but this needs further investigation. Two species of conservation concern, C. philippinense and S. ovata, are categorized as endangered and near-threatened species, respectively.